ANTROPOMETRIK PENEBANG JATI DI BKPH BANDUNGSARI KPH PURWODADI PERUM PERHUTANI UNIT JAWATENGAH - Sona Suhartana; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1990)
Anthropometric  data  of  the  workers  are essential  in  the practice of  ergonomics,  especially  for  the  design of  work places,  machines  and equipment in order to attain work comfort and increased  work productivity.Anthropometric measurements were carried out to 18 teak loggers aging between  20-35 years. The measurements included: body,  shoulder, elbow  and hip  height;  shoulder  and hip  width; length  of arm and. hand, length  of upper arm, lower arm and  hand;upper   reach  and  arm  span (measurements in  standing   position).   In  sitting  position, the  body measurements comprised  sitting,  elbow,  hip and knee  height;  length  of upper and lower log.The  result shoures  that  elbow  height  of  teak  logger has high  variability  and decreo,se their working comfort and productivity.  Lenght of arm and hand  which  are longer than axe handle  on the other hand speed  up working  fatique  and infficient work.